Frequency modulation (FM) transmitter and receiver - Goh, Han Shin (University Malaysia Sarawak (UNIMAS), 1998)
FM transmitter-receiver is indeed an electronic project that places great emphasis on practical work. Theoretical knowledge such as circuit theory, amplifier and principles of telecommunication learned several courses offered by Electronics and Telecommunications program is applied in the project.